HUMAN EXISTENTIALISM AND ARTIFICIAL INTELLIGENCE (AI) (Architecture Image Studies, 2026)
This study is about the relationship between humans and technology, particularly explaining the existential aspects of humans and artificial intelligence (AI). Based on the collaboration between humans and technology, artificial intelligence (AI) has a paradoxical side for human existence: on the one hand, it drives change towards existentialism, and on the other hand, it drives destruction and even the elimination of human existence. This research, which uses the philosophy of existentialism and the thoughts of Martin Heidegger's philosophy of technology and the philosophy of human existentialism from Jean-Paul Sartre, attempts to examine the function of control and exploitation of technology towards humans, which results in the loss of human authenticity. At the beginning of the article, it discusses what artificial intelligence (AI) is and the understanding of human existentialism, then discusses the vital and fatal impacts of AI on human existence. The findings in this study are that the most frightening thing about the development of Artificial Intelligence (AI) is not technology but a calculative way of thinking that results in the annihilation of everything, including human existentialism and the human ecosystem.